Corneal Neurotization: Essentials for The Facial Paralysis Surgeon - Crabtree, Jordan R.; Mulenga, Chilando; Tran, Khoa; Hussain, Arif; Boente, Charline S.; Ali, Asim; Feinberg, Konstantin; Borschel, Gregory H. (Facial Plastic Surgery, 2024)
Deficits in corneal innervation lead to neurotrophic keratopathy (NK). NK is frequently associated with facial palsy, and corneal damage can be accelerated by facial palsy deficits. Corneal nerves are important regulators of limbal stem cells, which play a critical role in epithelial maintenance and healing. Nonsurgical treatments of NK have undergone recent innovation, and growth factors implicated in corneal epithelial renewal are a promising therapeutic avenue. However, surgical intervention with corneal neurotization (CN) remains the only definitive treatment of NK. CN involves the transfer of unaffected sensory donor nerve branches to the affected cornea, and a variety of donor nerves and approaches have been described. CN can be performed in a direct or indirect manner; employ the supraorbital, supratrochlear, infraorbital, or great auricular nerves; and utilize autograft, allograft, or nerve transfer alone. Unfortunately, comparative studies of these factors are limited due to the procedure's novelty and varied recovery timelines after CN. Regardless of the chosen approach, CN has been shown to be a safe and effective procedure to restore corneal sensation and improve visual acuity in patients with NK.
Keywords: neurotrophic keratopathy; corneal neurotization; corneal sensation; anesthetic cornea; corneal nerve